Learning Facilities that Can Develop Science Process Skills in Indonesia : Review of Experimental Studies - Muhammad Syazali; Muhammad Erfan; Baiq Niswatul Khair (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
Aims of this study are to analyze: (1) types of learning facilities, (2) variants of each type of learning facilities, and (3) recommendations for implementation of variants of types of learning facilities that are empirically proven to be effective in developing the science process skills of students in Indonesia. This research is a literature review study. The data sources are articles in journals and proceedings published from 2016 to 20120. The articles that have been collected are then analyzed using the thematic method. Learning facilities consist of 7 types, namely strategies, approaches, models, methods, media, and learning aids. In total there are 106 variants with details of 7 variants of the type of strategy, 7 variants of the type of approach, 34 variants of the type of model, 11 variants of the type of method, 28 variants of the type of media, 5 variants of the type of teaching aid, and 15 variants of the type of learning device. From these various variants, there are 7 variants that are recommended to be used in facilitating students and students in developing their SPS. The variants are guided inquiry learning models, inquiry, PBL, PjBL and learning cycles, as well as learning media variants of modules and worksheets. This review is useful as a reference for teachers and lecturers because it provides various choices of learning facilities that can be applied to improve science process skills. The many choices help them to match the characteristics of the learners to be facilitated, their ability to implement, and the availability of infrastructure.